Alvajry Haris, Sultan, Fitri - Alvajry Haris; Sultan; Fitri (BJRM (Bongaya Journal of Research in Management), 2025)
This research is entitled "Marketing Strategy Analysis to Increase Indihome Sales at PT Alcom in the Makassar City Area." The purpose of this study is to analyze and implement marketing strategies using the Business Model Canvas (BMC) approach to increase Indihome service sales at PT Alcom in the Makassar City area. This study uses a qualitative approach with descriptive qualitative research. Data were collected through observation, interviews, and relevant documentation.The results of this study indicate that through the application of the Business Model Canvas, PT Alcom needs to strengthen several key elements such as customer segments, value propositions, channels, customer relationships, revenue sources, key resources, key activities, key partnerships, and cost structure to ensure efficient company operations.The key conclusions are to increase the sales force, improve the effectiveness of social media advertising, provide responsive customer service, and ensure optimal performance of installation technician partners. This strategy is expected to support increased sales and the company's competitiveness in the internet service market.  Keywords: Marketing Strategy, Business Model Canvas, Indihome, PT Alcom, Sales.